Assessment of noise emission levels in a selected wood processing laboratory (2018)
The study is designed to evaluate the noise levels of locally fabricated wood working machines in the wood processing laboratory of the department of agricultural and environmental engineering, university of ibadan, nigeria. maximum, minimum and average noise levels at the source were measured and recorded using a noise meter for a period of 10-20 minutes operation of each machine in the laboratory, and at sampled locations around the laboratory at distances of 5 – 30m at 5m interval during critical operating conditions of the machines. the results revealed that average noise levels from planing/thicknessing and grinding machines were above the generally advocated safe limit of 90db(a). people engaging in different teaching and educational activities in buildings that are more than 10m away from the laboratory were not exposed even during critical operating conditions. it is recommended that noise preventive measures should be implemented in the laboratory before resorting to orientate the workers on the use of protective equipment as this is a precursor to improving quality of life of workers and to ensure environmental sustainability.